" Mothers level of awareness and implementation of the first three objectives of education for all (EFA) goals 1 in Nigeria " (2009)
" Early Childhood Care and Education should comprise of childcare, mother care, pre and post-natal care, health and nutrition, family/community sensitization and support and the child's socialization at the pre-primary school. Thus, limiting its scope to mere pre-schooling could result to disregarding the factors that make school readiness possible. Four hundred and fifty mothers of children from birth to 6 years and 450 children selected from 36 public and private pre-primary school and 18 Day Care Centres were used. Parental Awareness of Early Childhood Care and Development Provision Questionnaire (PAECCDPQ) for mothers of children from birth to 3 years and those from 4 to 6 years and structured interview schedules were used. Majority of the mothers from both cohorts indicated some levels of awareness of indicators of some aspect of objectives of Education For All (EFA) Goal 1, except for provision of food for children by the government in schools. There is significant difference in the level of awareness as indicated by the mothers from both cohorts. All the mothers agreed that some aspects of EFA Goal 1 have been implemented to some great extent. Implications of the findings were also discussed. "